DEVELOPING AND THE ANALYSIS OF MATHEMATICAL MODELS OF GENERATORS OF LINEAR AND RECIPROCATING TYPES WITH ELECTROMAGNETIC EXCITATION - A. B. Menzhinski; A. N. Malashin; Yu. V. Suhodolov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
The mathematical modeling of generators of linear and reciprocating types with electromagnetic excitation resulted in obtaining the equivalent electrical circuit and diagrams of magnetic circuit of generators as well as the expressions that describe the electromagnetic processes in generators of linear and reciprocating types with electromagnetic excitation is presented in the article. Mathematical models of generators of linear and reciprocating types with electromagnetic excitation take into account the geometrical parameters of the magnetic system of generators, effect of the armature reaction, the unequal distribution of the magnetic field in the magnetic system of the generators and the dependence of the scattering coefficient and the fringe effect (in linear generators) and buckling (in the reciprocating electric generators) on the coordinates of the movement. An evaluation of the effectiveness of the generators of linear and reciprocating types with electromagnetic excitation was performed that demonstrated that the efficiency of the reciprocating generator with electromagnetic excitation is limited to the amount of movement of the moving part of the generator that can be considered as a drawback of this type of generators. Therefore, the reciprocating generator with electromagnetic excitation is more effective to be used in a small value of the working stroke of the movable part of it or in conjunction with a linear generator as a compensator of the end effect in reciprocating motion. In the linear generator the rate of change of inductance and mutual inductance throughout the movement of the moving part is practically constant. So if an increase of the magnitude of the working stroke of the movable part takes place the benefits of the linear generator are undeniable. However, it should be noted that a reduction of the stroke magnitude of the movable part of the linear generator is limited by constructional dimensions of the magnetic system of the generator, which reduces its efficiency at low value of the working stroke of the movable part.